The big house: image and reality of the American prison - Cox, Stephen D. (Icons of America)
Touring the institution -- How to build a big house -- Your life as a convict -- The art of humiliation -- Sex -- You built it, now try to run it -- A tale of two prisons -- Rajahs and reformers -- Prisons you can't tear down